From total work of art to the synthesis of arts - Gabriel, Marcos Faccioli [UNESP] (FapUNIFESP (SciELO), 2020)
There had been througout the 20th century a persistent recurrence of the theme of the synthesis or integration of arts, in the field of architecture at least. It was present amongst the early twentieth century vanguards but had a bounce back in the early postwar period with Le Corbusier, Sigfried Giedion and Fernand Léger. In Brazil in the 1950s, art critic Mário Pedrosa under the mote Brasilia enthusiastically hailed the construction of Brasília the New City, Synthesis of Arts (1981b, p. 355-363). The corresponding literature points out to architect and historian Gottfried Semper, a nineteenth century theorist of style, who cooperated closely with composer and operist Richard Wagner as the authors who put forth the original conceptions of the Gesamtkunstwerk or total artwork. In this study, we examine the speculative guise with which Wagner held up the Gesamtkunstwerk, as a strategic step for the studies on the theme.
Da obra de arte total à síntese das artes
Keywords: Architectural theory; Gesamtkunstwerk; Historical avant-garde; Integration of arts; Synthesis of arts